2022
DOI: 10.1037/edu0000637
|View full text |Cite
|
Sign up to set email alerts
|

Achievement emotions and academic achievement: Reciprocal relations and the moderating influence of academic buoyancy.

Abstract: The version presented here may differ from the published version or from the version of the record. Please see the repository URL above for details on accessing the published version and note that access may require a subscription.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0
5

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(44 citation statements)
references
References 110 publications
(204 reference statements)
0
39
0
5
Order By: Relevance
“…Moreover, it is worth noting that detecting different links between boredom and performance in the two examined settings can also shed some light on the reasons underlying some inconsistent results of previous research involving primary-school students, in which boredom was not examined according to different settings (Di Leo et al, 2019;Lichtenfeld et al, 2012;Muis, Psaradellis, et al, 2015;Muis, Ranellucci, et al, 2015;Obergriesser & Stoeger, 2016;Putwain et al, 2018Putwain et al, , 2020Putwain et al, , 2021Raccanello et al, 2019;Robertson et al, 2004;Zaccoletti et al, 2020). Distinguishing homework and tests might have helped to identify another moderator of the relations between boredom and performance, that is, setting, which has been frequently neglected in previous literature (for an exception, see Raccanello et al, 2013).…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Moreover, it is worth noting that detecting different links between boredom and performance in the two examined settings can also shed some light on the reasons underlying some inconsistent results of previous research involving primary-school students, in which boredom was not examined according to different settings (Di Leo et al, 2019;Lichtenfeld et al, 2012;Muis, Psaradellis, et al, 2015;Muis, Ranellucci, et al, 2015;Obergriesser & Stoeger, 2016;Putwain et al, 2018Putwain et al, , 2020Putwain et al, , 2021Raccanello et al, 2019;Robertson et al, 2004;Zaccoletti et al, 2020). Distinguishing homework and tests might have helped to identify another moderator of the relations between boredom and performance, that is, setting, which has been frequently neglected in previous literature (for an exception, see Raccanello et al, 2013).…”
Section: Discussionmentioning
confidence: 90%
“…For example, in mathematics boredom is linked to academic performance as evidenced by small to moderate negative correlations (ranging from À.16 to À.42) as well as by small positive correlations (Di Leo et al, 2019;Lichtenfeld et al, 2012;Muis, Psaradellis, Lajoie, Di Leo, & Chevrier, 2015;Putwain et al, 2018;Raccanello et al, 2019). In other cases, researchers found that achievement predicted boredom but not vice versa (Putwain et al, 2021;Putwain, Wood, & Pekrun, 2020). For science learning, small negative correlations emerged (Obergriesser & Stoeger, 2016).…”
Section: Appraisals and Outcomes Of Boredommentioning
confidence: 99%
“…Compared to GPA, standardized testing is assumed to be a more objective and a useful measure of students’ achievement [ 43 , 69 ]; however, its ability to adequately capture acquired knowledge and skills is limited [ 70 , 71 ]. Studies have shown that certain individual characteristics of children are more sensitive to a particular assessment method of achievement [ 72 , 73 ]. Therefore, both the teacher-assigned grades and standardized testing reflect different aspects of academic performance.…”
Section: Introductionmentioning
confidence: 99%
“…Second, previous studies have focused on exploring protective mechanisms in the stress and learning relationships among students (e.g., Putwain et al, 2020;Zhu et al, 2017), yet the protective role of students' FTP has not been studied in this respect-particularly with regard to their investment in learning. Our study provides evidence that even when students focused more positively on their future thoughts, feelings, and behavioral intentions in school and in their professional career, this did not help to reduce the negative impact of anxiety on their investment in learning for mathematics.…”
Section: Practical Implicationsmentioning
confidence: 99%
“…Overall, the different relationships between anxiety and learning may suggest that anxiety does not have the same effect on all students and that there are other factors that are involved as possible moderators within the anxiety and learning relationship. Recent studies suggest that certain individual difference variables such as academic buoyancy and proactive personality moderate the relationship between anxiety and learning among students (e.g., Putwain et al, 2020;Zhu et al, 2017). Our study aims to contribute to this body of research.…”
Section: Introductionmentioning
confidence: 96%